Engineering for Surgery - Belfiore, Nicola Pio; Ursi, Pietro; Scorza, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue offers a little taste of the immense variety of an intrinsically vast and interdisciplinary subject, namely, the applications of engineering to surgery. Some of these have been successfully applied or are still under development, while we have been offered a preview of others thanks to the fantasy of creative science fiction writers. This Special Issue aims to stimulate the interest of engineers and surgeons, who will benefit from mutual advantages gained from their cooperation.